THE RELIGIOUS FACTOR IN THE «ARAB SPRING» - A. V. Krylov (Vestnik MGIMO-Universiteta)
A huge wave of mass protests for the last years has lead to a collapse of many longstanding traditional regimes in some Arab states (Egypt, Tunisia, Libya and Yemen). In other states (Syria, Bahrain, Jordan, Saudi Arabia, Algeria and Morocco) a serious aggravation of political situation occurred. Many experts in Russia as well as abroad share an opinion that the phenomenon of the “Arab revolution" or the so cold "Arab Spring" has the same basic pattern: after the beginning of unrest in North Africa and the Middle East the Islamist political parties, organizations and groups are gaining strength, popularity and influence. The main content of the article is focused on the analysis of religious, political, socio-economic and other aspects of the contemporary ideology and practice of the radical Islam, its threats and challenges. The current situation in the region has favored the creation of a new political alliance in the Greater Middle East. Now the US administration's policy in the Middle East is aimed at the advancement of the of the radical Islam front to Iran, North Caucasus region and Central Asia. This policy corresponds to the global strategic interests of the U.S. regional partners including Petro-Islamic States, Turkey and even Israel. Analyzing the situation around Syria the author notes that the steps undertaken by the members of the new regional alliance to eliminate B. Assad - another victim of the "Arab Spring" – can, first of all, aggravate an extremely unstable situation in Syria, and, secondly, create a real perspective of the radical Islam advancement right up to the borders of the Russian Federation.